2008
DOI: 10.1002/adma.200800757
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Strong, Electrically Conductive, and Biocompatible Graphene Paper

Abstract: Research on graphene was originally motivated by its peculiar electrical transport properties and the promise of future applications in nanoelectronics. [1,2] Graphene sheets, owing to their exceptional thermal and mechanical properties and high electrical conductivity, are also of great interest to serve as new nanoscale building blocks to create unique macroscopic materials. [3][4][5] Recent studies have shown that graphene sheets can be prepared in large quantity through chemical conversion from graphite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
1,231
16
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,917 publications
(1,327 citation statements)
references
References 36 publications
52
1,231
16
6
Order By: Relevance
“…High-resolution transmission electron microscopy (HRTEM) analysis (Fig. 2a) revealed that the graphene sheets in the cell wall are well oriented in a nearly parallel manner, similar to the layered structure observed in the ultrastrong graphene paper prepared under the directional flow 35,36 .…”
Section: Resultsmentioning
confidence: 52%
“…High-resolution transmission electron microscopy (HRTEM) analysis (Fig. 2a) revealed that the graphene sheets in the cell wall are well oriented in a nearly parallel manner, similar to the layered structure observed in the ultrastrong graphene paper prepared under the directional flow 35,36 .…”
Section: Resultsmentioning
confidence: 52%
“…Schniepp et al 40 observed that below 500°C, the C/O ratio for the product obtained was no more than 7, and with temperatures that reached 750°C, the C/O ratio was higher than 13. Li et al 68 observed an effect of thermal annealing of foils prepared from aqueous dispersions of CCG. Conductivity improved from~40 tõ 350 S cm − 1 after treatment at 500°C.…”
Section: Thermal Reductionmentioning
confidence: 99%
“…[1,2] The extraordinary properties of this intriguing material have been used to provide advantage in numerous areas including composites, energy storage and conversion, nanoelectronics, sensors, biosensors, as a support for catalysts and transparent conducting films. [1,[3][4][5][6][7][8][9] However, in all of these studies, the performance levels obtained are limited by the ability to translate the properties inherent in graphene nanocomponents into the macroscopic structures needed for practical applications. [4] In this context, the recent discovery of liquid crystalline (LC) behavior of graphene oxide (GO) dispersions in various organic, [8] and aqueous media brings added control to the assembly of larger structures using the chemical process approach.…”
Section: Introductionmentioning
confidence: 99%
“…[1,[3][4][5][6][7][8][9] However, in all of these studies, the performance levels obtained are limited by the ability to translate the properties inherent in graphene nanocomponents into the macroscopic structures needed for practical applications. [4] In this context, the recent discovery of liquid crystalline (LC) behavior of graphene oxide (GO) dispersions in various organic, [8] and aqueous media brings added control to the assembly of larger structures using the chemical process approach. [10][11][12][13][14][15][16] The LC state can be used to direct the ordered assembly of nanocomponents in macroscopic structures via simple methods like wet-spinning.…”
Section: Introductionmentioning
confidence: 99%